When green leadership matters: The role of knowledge absorption and creativity in green product development - Utik Bidayati; Muhammad Ali Fikri; Desta Rizky Kusuma (Universitas Islam Malang, 2025)
This study examines the relationship between green transformational leadership (GTL) and green product development performance (GPDP), with green absorptive capacity (GAC) and green creativity (GC) serving as mediating mechanisms. Previous studies often treat creativity as a direct factor in product development, which leaves a limited understanding of how leadership values are translated into concrete outcomes. To address this issue, this research uses a quantitative survey approach with purposive sampling based on business experience, ownership status, and participation in environmental training. The study involved 165 owners and managers of batik Micro, Small, and Medium Enterprises (MSMEs) in Yogyakarta, Indonesia, and the data were analysed using PLS-SEM. The results show that GTL is positively related to GPDP; however, this relationship does not operate directly but is partly channelled through the ability of business actors to absorb environmental knowledge (GAC) and process it into creative ideas and practices (GC). Thus, the findings suggest that green leadership leads to tangible improvements in environmentally friendly product development only when knowledge from training and production experience is properly understood and applied in daily practices. Accordingly, the practical implication of this study is that environmental training programs should be closely integrated with everyday production activities, rather than focusing solely on awareness or normative commitment among MSME actors.